Women Stereotypes Portrayal in Gurnah’s Afterlives - Aisyah Roudlatul Jannah; Sufi Ikrima Sa'adah (Universitas 17 Agustus 1945 Surabaya, 2026)
The objective of this research is to reveal any kind of women stereotypes and the impact of defying that stereotypes in Gurnah’s Afterlives. This research applies a descriptive qualitative method in analyzing the data. The data were obtained from the original novel and were presented in the form of a quotation sentence. After the data collection, the data were analyzed through deep reading and were interpreted carefully based on a feminist literary criticism approach. There were found two kinds of women stereotypes were found, from a general one, which is African women stereotypes, to the specific one, which is African muslim women stereotypes. African women in the novel are expected to do chores, portrayed as careless human beings, and not allowed to be educated in the sense of being able to write, which is believed as men’s business. African muslim women in the novel are often arranged into marriage, are expected to marry at a young age, prohibited from being out of the home for a long time and required to behave properly. Moreover, the women characters in this novel who have defied the stereotypes will face unpleasant treatment, such as being tortured or rumored. By analyzing women stereotypes in the novel, it reveals new insight into the existing women stereotypes in Africa, whether they are muslim or not.